Economic Analysis and Forecasting in the Global Economy and in Emerging and Developing Regions Including Africa: How Informative is the Ifo World Economic Survey (WES)? - Johanna Garnitz; Willi Leibfritz (Center for Economic Studies and ifo Institute (CESifo), 2016)
Economists around the world rely in addition to official statistics on business (and consumer) surveys, which are more up-to-date. However, for many emerging and developing countries there is a lack of such surveys. This gap can, at least partly, be filled by the Ifo World Economic Survey (WES). In this paper we first describe this survey and also examine how helpful it is for macroeconomic analysis and short-term forecasting. We find that this survey provides important up-to-date information about the cyclical stage of the global economy and of major emerging and developing regions including Africa. Increasing the number of participating experts could further improve its usefulness for macroeconomic analysis in these regions.
Keywords: E01; F01; N14; N15; N16; N17; 330; macroeconomic analysis; business cycle; global economy; emerging and developing countries; Africa